Identification and Activity of The Retrotranposon Tos17 in Indonesian Javanica Rice CV. Rojolele and Japonica Rice CV. Gajahmungkur - Nugroho, Satya; Loedin, Inez Hortenza Slamet; Ouwerkerk, Pieter B. F. (Annales Bogorienses, 2007)
Retrotransposons are mobile genetic elements that transpose via an RNA intermediate that is revers transcribed before integration into a new location within the host genome. They are ubiquitous in eukaryotic organisms and constitute a major portion of the nuclear genome (often more than half of the total DNA) in plants. Tos17 is a rice endogenous retrotransposon that has been studied thoroughly. Tos17 has been shown to be an efficient insertional mutagen and saturation mutagenesis tool for gene tagging and functional genomics in Japonica rice cv nipponbare. In Javanica rice, however, the presence and activity of Tos17 has not been described thus far. while in some Indica rice Tos17 has been found to be inactive. Javanica rice, also known as tropical Japonica rice, has many cultivars which may serve as potential genetic resources of great interest for breeding programmes. Here, the presence and activities of retrotransposon Tos17 in Javanica rice cv Rojolele was described and compared to those of Japonica rice and Japonica rice cv Gajahmungkur. We identified five and three copies of Tos17 in Rojolele and Gajahmungkur, respectively, with different activities.